Groundwater Quality Sustainability. - Zuber, Andrzej (Hydrogeology (International Association of Hydrogeologists), 2012)
Sustainable groundwater development requires knowledge of the appropriate recharge and transport-processes. This is a prerequisite to understanding: (i) groundwater resources and their availability, and (ii) the dependence between groundwater and the environment. Conceptual understanding of groundwater flow at both temporal and spatial scales (local and regional) is essential for management that will support engineering, industry, agriculture, ecology, and all environmentally related issues. This book has been prepared for scientists, researchers, students, engineers, water resources specialis.